Pendekatan Konsep Restorative Justice Dan Pemenuhan Hak Dalam Proses Peradilan Anak (Menurut UU No. 11 Tahun 2012) - Muhammad Surya Adi Wibowo; Drs. M. Yunus (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
AbstractThe judicial process children give priority to the concept of restorative justice in the implementation as an effort to continue to maintain the future children , but the rights of the child in the judicial process that is often ignored .The problems that have arisen how the implementation of the concept restorative justice in the judicial process for violation of children and how the protection of the law that will be given to the rights of children as regulated in the law number 11 2012 about child criminal justice systems .The purpose of which are how the judicial process and protection of what they were by the son .Usefulness for providing information on the judicial process and legal protection for children in accordance with the regulations .By using the method juridical normative , obtained the results of research regarding the application of the concept of restorative justie in the judicial process children often find various obstacles because involves various parties. Keyword: Protection of Law, The Rights of Child, Restorative justice